Migraine and Neuroticism: A Scoping Review - Carmen M. Galvez-Sánchez; Casandra I. Montoro Aguilar (Behavioral Sciences, 2022)
Headache is the first cause of consultation in neurology, and one of the most frequent reasons for consultation in general medicine. Migraine is one of the most common, prevalent, and socioeconomically impactful disabling primary headache disorders. Neuroticism can be conceptualized as a disposition to suffer anxiety and emotional disorders in general. Neuroticism has been associated with various mental and physical disorders (e.g., chronic pain, depression), including migraine. With the aim to explore in depth the relationship between migraine and neuroticism, and contribute to the understanding of this relation in order to provide a better treatment for migraine patients based on a personalized and more comprehensive approach, a scoping review was performed using PubMed, Scopus, and Web of Science. Databases were searched independently by the two researchers, reaching a final set of 18 articles to be included. The search terms were: migraine and neuroticism. Neuroticism seems to be highly prevalent in migraine patients. Findings reveal that migraine patients with comorbid depression and anxiety showed higher levels of neuroticism. Depression has been associated with an increased risk of transformation from episodic to chronic migraine whereas neuroticism might be a mediator factor. Neuroticism also might be a mediator factor between childhood maltreatment and migraine. The revision conducted confirms that: (1) Migraine patients usually have a higher level of neuroticism and vulnerability to negative affect, compared to non-migraineurs and tension-type headache patients. (2) Neuroticism is associated with migraine. Nonetheless, more research is needed to clarify potential moderators of this relationship and the role of neuroticism itself in this disease. This knowledge might be useful in order to promote a better management of negative emotions as part of intervention programs in migraine.